The rule of the clan : what an ancient form of social organization reveals about the future of individual freedom - Weiner, Mark Stuart (New York : Farrar, Straus and Giroux, 2013)
A revealing look at the role kin-based societies have played throughout history and around the world. It examines the constitutional principles and cultural institutions from medieval Iceland to modern Pakistan.
Individualism's paradox -- From clan to club -- National security and clan honor -- Law without a state : the Nuer of Southern Sudan -- A state without a king : medieval Iceland -- Clannism and democratic reform : the Palestinian authority -- Solidarity, group honor, and shame : modern India, Pakistan, and Afghanistan -- Feud as an instrument of harmony : the Philippines -- The king to king : state development in Anglo-Saxon England -- "We have made you into nations and tribes" : the vision of early Islam -- The romance of the clan -- The clan's return.
Includes bibliographical references and index.
Keywords: Clans -- Social aspects; Clans -- Political aspects; Kinship -- Social aspects; Kinship -- Political aspects; Customary law; Law, Primitive; Democracy